Optimized Sample Preparation Technique For Visualization Of The Adherence Of Lactobacillaceae Sp. To Human Colorectal Adenocarcinoma Cell Line Ht-29 By Field Emission Scanning Electron Microscope - Ilyanie H.Y; Ida Muryany M.Y.; Huda-Faujan N. (The Malaysian Society for Biochemistry & Molecular, 2024)
Malaysian Journal of Biochemistry & Molecular Biology, Volume 1(Special issue), Page (16–22)